Communities of Knowing: Curriculum Making in/of Community (LEARNing Landscapes, 2019)
This paper explores experiences of becoming a “curriculum maker of community” as part of the University of Alberta’s Building Peaceful Communities Summer Institute, held annually over a two-week period each July. Prompted by the experience in 2018, the author explores the ways in which curriculum can be co-composed as a community of learners, moving beyond prescripted curriculum. Throughout the account, the author narrates autobiographical life experiences that serve to illustrate ways of knowing and ways of coming to communities of knowing.
Keywords: community; curriculum; ways of knowing; narrative inquiry; interpretive inquiry